The Role of Supervisory Agency in the Circulation of Cosmetics With Fake Distribution Permission - Siti Khodijah; Nirwan Junus; Nurvazria Achir (Estudiante Law Journal, 2022)
This study aims to determine the role of the Food and Drug Supervisory Agency which (will be referred to as BPOM) in the distribution of cosmetics that include a fictitious distribution permit. The method used in this study is an empirical research methodology. This study uses a qualitative approach and sampling using purposive sampling and using descriptive analysis techniques. The results of this study show that the role of BPOM in the distribution of cosmetics that includes a fictitious distribution permit continues to carry out Supervision, Guidance, and Prosecution of every producer who violates government regulations related to the circulation of counterfeit cosmetics that include a fictitious distribution permit number and several programs are run to deceive consumers. get the right. In addition, it continues to protect consumers who experience losses by providing administrative sanctions to the perpetrators to be able to pay for the losses suffered by the consumers themselves. Protecting Consumers from the Circulation of Dangerous Cosmetics BPOM has several programs, namely the National Movement to Beware of Illegal Drugs and Food (GNWOMI), GENPOPA, BPOM Checks, Public Warnings, Educational Videos, Community Awareness Index Surveys, Implementing Teams for Quality Improvement of Community Empowerment and Consumer Protection.